Rehabilitasi Anak Berhadapan Dengan Hukum Dalam Perspektif Agama (Studi Kasus Metode Pengembangan Mental Spiritual Anak Lembaga Penyelenggaraan Kesejahteraan Sosial Anak Berhadapan Dengan Hukum (LPKS ABH) di Nganjuk - Nizaruddin Wajdi, Muh. Barid (STAI Miftahul Ula Nganjuk, 2017)
Abstract: This paper describes the stages of the implementation process of social rehabilitation of juvenile delinquents and children in conflict with the law. Social rehabilitation carried out to change the behavior of the client. The method used was qualitative research methods with descriptive studies in LPKS ABH Nganjuk. The results showed that social rehabilitation at the center of social rehabilitation, divided into eight phases of the rehabilitation process, the initial approach phase, admission, assessment, planning, intervention, implementation of interventions, resocialization, further guidance, and termination. In its implementation, there are factors inhibiting and supporting the social rehabilitation process conducted. Approach of Islamic spiritual is referred to as âIslamic psychotherapyâ, it is a process of treatment and healing of mental disorders, spiritual, moral and physical victims through the guidance of Allah, Prophets, and their heirs. Therefore, Islamic spiritual approach is wider to be developed.